Measurement and Analysis of Acoustic Surface Scattering for Oil Concentration - Ratna Juita Sari; Henry Munandar Manik; Susilohadi Susilohadi (Journal of Applied Geospatial Information, 2022)
The life of maritime flora and wildlife are substantially impacted by oil's effects, and this has an immediate impact on livelihoods. The impact disrupts the lives of contaminated coastal communities. Because of the potential losses caused by oil pollution, the government enacts policies governing environmental conditions in order to maintain or improve the quality of the polluted sea. The purpose of this study was to calculate the acoustic backscattering value of oil using a single beam echosounder and compare the measurement results from a single beam echosounder with the results of gravimetric analysis. The data acquisition was carried out in March 2021 at the Marine Acoustic Laboratory, Department of Marine Science and Technology, Faculty of Fisheries and Marine Sciences, IPB University, using the SIMRAD EK-15 frequency of 200 kHz and oil used as a source of pollution, namely the dexlite type (density of 880 kg/m3). The results showed that the value of Surface Backscattering Strength (SS) decreased when contaminated with oil, namely -63.76 dB and -65.90 dB, but when oil was added back, the SS value increased to -50.81 dB. The relationship between oil concentration and surface backscattering strength shows a negative correlation between the variables, and the level of the relationship between variables is 0.85.